DEVELOPMENT OF PENCAK SILAT LEARNING MEDIA BASED ON MACROMEDIA FLASH 8 - Nurul Ihsan; Riko Valentino (Gladi : Jurnal Ilmu Keolahragaan, 2019)
The purpose of this study is to develop an interactive multimedia on Pencak Silat materials using the application Macromedia Flash 8 for grade VIII and to find out the feasibility, practicality and effectiveness of learning media using Macromedia Flash 8. The development model used in this study is the development model of Borg and Gall. Applications based on the results of the validity test from the material experts obtained a value of 4.33 in the "Valid" category so that the material was declared good to use. From the results of the validity testing of media experts, it was obtained a value of 4.09 with the category "Valid". So that it can be concluded that this learning media is feasible and can be tested. Furthermore, based on the practicality test obtained an average of 4.05 with the category "Practical". The results of the effectiveness test, the results of tcount> ttable are 2.12> 1.73. So that it can be concluded that the interactive multimedia learning of Pencak Silat material grade VIII using the application of Macromedia Flash 8 is practical and effectively used as a learning media for Pencak Silat